p=9+6ln(4x+1)

Simple and best practice solution for p=9+6ln(4x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p=9+6ln(4x+1) equation:


Simplifying
p = 9 + 6ln(4x + 1)

Reorder the terms:
p = 9 + 6ln(1 + 4x)
p = 9 + (1 * 6ln + 4x * 6ln)
p = 9 + (6ln + 24lnx)

Solving
p = 9 + 6ln + 24lnx

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Simplifying
p = 9 + 6ln + 24lnx

See similar equations:

| x+5*5=3x*2 | | p^2-26p=41 | | 8-2=-3 | | .10n+12=.12n+10 | | 4x+5x+5+22= | | ln(x)=4.3+ln(6.1) | | 3n^2+16n+21= | | 1+4x=0 | | z^2-20z=0 | | x+6x(7x+1)=0 | | y=-7x+57 | | F(x)=74+3.7x | | 12x-24+8x+28=180 | | 61=5a-4 | | 2(x+4)(x+7)=(2x+1)(x-9) | | 2x^3-22x^2+60x=0 | | x(7x+5)-x=0 | | -4-11=7x+15-6x | | .03x+18000=90 | | 4(a-4)=2(a+5) | | -15=r-8 | | 7+2(x-3)-4x= | | y+1(9+24)-28=96 | | 5x+20=5x-18 | | 10+a=26 | | x(7x+5)-x(x)(x)=0 | | 5x^2+10x+8y^2-48y+37=0 | | 2(113-2c)+4c=226 | | 20+10x-(8x-12)=68 | | .03x+.07(18000-x)=90 | | 4k-(-6)=-2-(-16)-(-2) | | 6n-.7=11 |

Equations solver categories